Outcome of infants with antenatally detected hydronephrosis - Pushpalatha Kariyappa; Rajashekhar Basavaraj Kenganal; Sreejesh Lal Kizhakkayil (Indian Journal of Child Health, 2020)
Background: It is estimated that genitourinary anomalies comprise 20% of all antenatally detected fetal anomalies, of which hydronephrosis is the most common anomaly affecting 1–5% of all pregnancies. Depending on diagnostic criteria and gestation, the prevalence of antenatal hydronephrosis (ANH) ranges from 0.6 to 5.4%. Aim: The aim of the study was to find the causes and outcome of antenatally detected hydronephrosis. Methods: Babies diagnosed with antenatally detected hydronephrosis from January 2016 to December 2016 were followed up for 6 months postnatally. Based on anteroposterior diameter of renal pelvis babies were classified as mild, moderate and severe according to Society for Fetal Urology consensus statement on evaluation and management of ANH and these babies were followed up. Results: Two percent of babies born during the study period had significant ANH (68/3251). Three were lost to follow-up. Among the remaining 65 babies, three (4.6%) had severe, 13 (20%) had moderate, and 49 (75.4%) had mild ANH. During follow-up 39 (60%) resolved spontaneously, ten (15.3%) showed resolving hydronephrosis and 16 (24.6%) required some form of intervention. All babies with severe ANH required intervention (100%). Nine (69.2%) babies with moderate and four (8.1%) babies with mild ANH required intervention. Among babies who required intervention, majority had vesicoureteric reflux (12.3%) and pelviureteric junction obstruction (9.2%). Sixteen babies (24.6%) developed urinary tract infection. Conclusion: Majority of the ANH are mild and resolve spontaneously. Size at detection decides the likelihood of need for intervention as all those with severe hydronephrosis required intervention. Majority of babies with ANH are asymptomatic at birth and postnatal abnormality could be detected only by follow-up scans. Hence, this study reinforces on the regular follow-up of babies with ANH.